Forecasting the impact of U.S. tariff hikes on Malaysian palm oil exports: a scenario-based approach - Duasa, Jarita; Ahmad, Azlin Alisa; Idris, Zera Zuryana; Mohd Thas Thaker, Mohamed Asmy (Human Resource Management Academic Research Society (HRMARS), 2025)
This study investigates the potential economic impact of the United States' decision to raise import tariffs on Malaysian palm oil from 10% to 19%, effective August 1, 2025. Utilizing scenario-based forecasting and univariate time-series models, the analysis evaluates Malaysia’s palm oil export value and the corresponding U.S. import value from 1989 to 2024, with forecasts extending through 2030. Two scenarios are simulated: a baseline scenario assuming the continuation of a 10% tariff and a shock scenario reflecting the 19% tariff hike. The results indicate significant projected revenue losses under the shock scenario—approximately USD 434,950 in export earnings and USD 2.69 million in U.S. import value over the six-year forecast period. These findings highlight the vulnerability of Malaysia’s palm oil industry to protectionist trade policies and emphasize the need for strategic diversification, value-added export development, and proactive trade diplomacy. The study contributes empirical evidence to inform policy decisions in the face of external trade shocks.